2018
DOI: 10.1016/j.actatropica.2018.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Fasciola hepatica glutathione S-transferase as an antigen for serodiagnosis of human chronic fascioliasis

Abstract: Due to the unsatisfactory performance of parasitological diagnosis of human fascioliasis; the use of immunodiagnosis based on the detection of anti-Fasciola antibodies is traditionally used as a diagnostic alternative using total or purified parasite excretory-secretory products (ESPs). Glutathione S-transferase (GST) protein, one of the F. hepatica ESP components, possesses well-known roles in the detoxification of xenobiotic and endogenously derived toxins within the host bile environment. GST has shown to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 60 publications
0
21
0
4
Order By: Relevance
“…Our group and others have applied a method based on GSH-affinity chromatography as part of the strategy to identify GST isoforms from a cytosolic extract of F . hepatica 14,16 . In the present study, the protein was purified in active form with an average specific enzymatic activity of ~35 Units/min/mg (two separate batches) and when analyzed by 12.5% SDS-PAGE, it showed a single homogenous polypeptide band of ~25 kDa with a high purity level (96.17%) as demonstrated by the iBAQ value from the nano-LC MS/MS analysis 17 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our group and others have applied a method based on GSH-affinity chromatography as part of the strategy to identify GST isoforms from a cytosolic extract of F . hepatica 14,16 . In the present study, the protein was purified in active form with an average specific enzymatic activity of ~35 Units/min/mg (two separate batches) and when analyzed by 12.5% SDS-PAGE, it showed a single homogenous polypeptide band of ~25 kDa with a high purity level (96.17%) as demonstrated by the iBAQ value from the nano-LC MS/MS analysis 17 .…”
Section: Resultsmentioning
confidence: 99%
“…This indicates that the capacity of nFhGST to block the LPS-stimulation of TLR4 is independent of its enzymatic activity, as well as its native secondary/tertiary structure. Additionally, because nFhGST is an immunogenic molecule capable of inducing antibodies during the active infection 16 , we wanted to ascertain whether the presence of high levels of anti-nFhGST antibodies could impact the antagonistic capacity of this molecule on TLR4. To answer this question, THP1-Blue CD14 cells were incubated with different dilutions of an anti-nFhGST serum followed by the addition of nFhGST and the stimulation with LPS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the liver is an organ of intense metabolic activity and is precisely the place where juvenile and adult stages of F. hepatica localize. Therefore, the parasite may be damaged by the attack of xenobiotics during the normal metabolism of the host, so GST is essential for the survival of F. hepatica in the liver of the host (Vasti et al 2018 ). Our results showed that GST was not only expressed in somatic proteins of JF, IF, and AD of F. hepatica which colonized in the liver of the host, but also expressed in MC which survived in the external water environment.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, GSTs have been widely used as biomarkers of toxicity [13] and in pharmaceutical industries to scavenge organic hydroperoxides and ROS [14]. Furthermore, GSTs have been used as an indicator of certain diseases, especially hepatic infection [15]. Therefore, GSTs have different biological activities due to the differences of the conserved sequence regions, substrate specificity, and biochemical characterizations.…”
Section: Introductionmentioning
confidence: 99%